Carotenoides e clorofilas microalgais: ênfase na caracterização e bioacessibilidade - Fernandes, Andrêssa Silva (2021)
Microalgae are sustainable biometabolic factories for the production of a variety of bioproducts such as proteins, carbohydrates, fatty acids and mainly bioactive molecules that can have beneficial effects on human health, such as pigments. Thus, biodiversity and microalgae ecology represents an opportunity to face several challenges that society today is claiming regarding the demands for food products beyond basic nutrition. Among the classes of natural pigments, carotenoids are the most studied, and few studies are devoted to the profile of chlorophylls. Moreover, considering the significant number of species available for exploration, there are still few studies in this research field where a considerable number of strains remain under-explored. Given this scenario, this work is based on an exploratory study on the characterization of the profile of carotenoids and chlorophylls in microalgae species and determining the bioaccessibility of these compounds to guide their use in functional and nutraceutical products. As a result, five articles and two book chapters (published or in the publication process) were generated, which were organized in this document into chapters. Chapters 2 to 6 refer to articles, and chapters 7 and 8 refer to book contributions. Chapter 2: “An overview of microalgae carotenoids and chlorophylls: focus on bioaccessibility” (review article in the process of publication); Chapter 3: “HPLC-PDA-MS/MS as a strategy to characterize and quantify natural pigments from microalgae” (research article/publication completed); Chapter 4: “Determination of the profile of chlorophyll compounds in microalgae species” (research article/publication completed); Chapter 5: “Insights on the intestinal absorption of chlorophyll series from microalgae” (research article/publication completed); Chapter 6: “Bioaccessibility of microalgae-based carotenoids and their association with the lipid matrix” (research article/publication completed); Chapter 7: “Carotenoids: “A brief overview on its structure, biosynthesis, synthesis, and applications” (published book chapter); Chapter 8: “Chlorophylls as food additives” (published book chapter). The results of these scientific productions indicate that microalgae synthesize a variety of carotenoids and chlorophylls, many of these structures specific to these microorganisms and with important bioactive properties prominent in human health. Many of these compounds were identified for the first time in the species evaluated. Differences in the carotenoids and chlorophylls profile were observed among microalgae species, demonstrating that each species has a unique biochemical constitution. The bioaccessibility of these compounds also varied according to the microalgae species and nature of the product digested. Above all, microalgae carotenoids and chlorophylls proved to be bioaccessible both from microalgae biomass like from isolated extracts. Chlorophylls have also been shown to be efficiently uptake by Caco-2 cells. In fact, these results reinforce the metabolic diversity of microalgae, their biotechnological potential and indicate these microorganisms as promising sources of a diversity of natural carotenoids and chlorophylls to be heavily exploited for purposes that aim at food and health. Finally, this study can assist in the formulation and future development of new natural, functional, and nutraceutical foods and products from microalgae-based ingredients.